Pengembangan Media Permainan Fruit word puzzle pada Pembelajaran Bahasa Indonesia pada Siswa Tunarungu di SDN Mojorejo 1 Kota Batu - Arianti, Fina; Suwandayani, Beti Istanti; Mukhlishina, Innany (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to find out whether the fruit word puzzle game media can be used as a learning medium in Indonesian language learning, to find out the reactions of deaf students to the use of fruit word puzzle game media, and to develop the fruit word puzzle game media for deaf students. The method used in this research is development or Research and Development (R&D), using the ADDIE development model (Analysis, Design, Develop, Implementation and Evaluation). The subject of this research uses a single subject. Research data collection methods include interviews, observation, observation sheets on 3 aspects (cognitive, psychomotor and affective aspects), and documentation. The results of the research show that the fruit word puzzle game media can be used as a learning medium in Indonesian language learning, deaf students give very strong reactions to the fruit word puzzle game media, and the fruit word puzzle game media is very valid, practical and effective for use with students deaf.